Affirming the Democratic Economic System After the Amendment of Article 33 of the Indonesian Constitution: A Critical Legal Studies Perspective - Atmaja, A.P. Edi; Erliyana, Anna (Faculty of Law Universitas Padjadjaran, 2024)
This paper, which uses an interdisciplinary, historical, and literary approach, aims to answer the questions of how the process of discussing changes to Article 33 of the Indonesian constitution led to the formulation of the article as it is known today. Second, how did the amendment of Article 33 of the Indonesian Constitution pave the way for the emergence of neoliberal legal products in Indonesia? Third, how is the democratic economic system (sistem ekonomi kerakyatan), as an economic system with a strong historical and constitutional foundation in Indonesia, affirmed by the deviationist doctrine from the perspective of critical legal studies (CLS)? This paper discusses the debates that took place in the agenda to amend Article 33 of the Indonesian constitution as the background of today's anomie. From a CLS perspective, the inclusion of the concept of efficiency in Article 33 of the Indonesian constitution after the amendment shows the infiltration of neoliberalism into Indonesia's basic law, riding on the political and legal reform agenda after the collapse of the authoritarian regime. To counter the excesses of neoliberalism, a legal scholar in the CLS perspective can engage in radical legal practice centred on the deviationist doctrine by, among other things, tracing legal principles back to their roots. Based on the deviationist doctrine, the formulation of Article 33 of the 1945 Constitution is a credo of political economy as well as the original legal policy of a sovereign, anti-colonialist, anti-imperialist, anti-capitalist independent state, and therefore cannot be arbitrarily changed and/or abolished.